Framing decisions in experiments on higher-order risk preferences - Alexander Haering (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
In this study I analyze how lottery framing and lottery display type affect the degree of higher-order risk preferences. I explore differences by comparing reduced and compound lottery framing, and by comparing lotteries in an urn-style and in a spinner-style display format. Overall, my findings show that individual behavior is influenced by lottery framing but not by display format. – – In dieser Studie analysiere ich, wie das Lotterie-Framing und die Art der Lotterie-Darstellung Risikopräferenzen höherer Ordnung beeinflussen. Ich vergleiche dabei reduzierte und zusammengesetzte Lotterien und eine Darstellung der Lotterien in Form von Urnen und in Form von Spinnern ('Glücksrädern'). Insgesamt zeigen meine Ergebnisse, dass individuelles Verhalten durch das Lotterie-Framing, aber nicht durch die Lotterie-Darstellung beeinflusst wird.
Keywords: C91; D81; 330; Risk aversion; prudence; temperance; higher-order risk preferences; lottery framing